1983
DOI: 10.6028/nbs.ir.83-2767
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the concentration of sulfur dioxide, nitrogen oxides, and ozone in the National Archives Building

Abstract: The figures consist of five figures that are plots of the concentration of oxides of nitrogen measured at different locations. These begin on page 15. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This is, of course, not the case. The concentration of pollutants in the stack atmosphere is known to fluctuate (2) and, in the case of , to follow the diurnal variations in the ambient District of Columbia environment (2). Hence, in this section we answer the question, "What happens when the exterior concentration is not constant?"…”
Section: 2 Exterior Conditions Vary With Timementioning
confidence: 99%
See 4 more Smart Citations
“…This is, of course, not the case. The concentration of pollutants in the stack atmosphere is known to fluctuate (2) and, in the case of , to follow the diurnal variations in the ambient District of Columbia environment (2). Hence, in this section we answer the question, "What happens when the exterior concentration is not constant?"…”
Section: 2 Exterior Conditions Vary With Timementioning
confidence: 99%
“…Certainly it is known that the cellulose molecule is oxidized by N 2 O 4 to form primarily a carboxyl at the C -6 position and secondarily aldehyde and ketone groups at other positions in the molecule (42) Other polymers are known to undergo chain scission by NOj (43,44), but the only work that we have found that relates to the degradation of paper is a study of the degradation of cotton fabric (45) In this work, cotton fabric was exposed at room temperature and normal humidity to atmospheres separately containing various concentrations of NO 2 …”
Section: Oxides Of Nitrogenmentioning
confidence: 99%
See 3 more Smart Citations